2022
DOI: 10.1111/hel.12886
|View full text |Cite
|
Sign up to set email alerts
|

Economic and health impacts of Helicobacter pylori eradication strategy for the treatment of peptic ulcer disease: A cost‐effectiveness analysis

Abstract: Background Most peptic ulcer cases are associated with Helicobacter pylori (H. pylori) infection or the use of nonsteroidal anti‐inflammatory drugs (NSAIDs). H. pylori eradication therapy is recommended for the treatment of H. pylori‐positive peptic ulcers. We aimed to assess and validate the cumulative economic and health effects of H. pylori eradication strategy for the treatment of peptic ulcers compared with PPI therapy strategy. Materials and Methods We developed a cohort state‐transition model for H. pyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Third, the RPUR was reported in only 12 of the 36 included RCTs, potentially impacting the accuracy of our findings. Fourth, it was known that factors such as patients’ age, current smoking and/or drinking habits, the locations and sizes of ulcers, antibiotic resistance of HP , various T/Q therapy regimens and recent use of non-steroidal anti-inflammatory drugs (NSAIDs) could be identified as the effect modifiers 76–78. Baseline comparisons between arms revealed no significant differences in patients’ ages or the locations and sizes of ulcers (see online supplemental table S2).…”
Section: Discussionmentioning
confidence: 99%
“…Third, the RPUR was reported in only 12 of the 36 included RCTs, potentially impacting the accuracy of our findings. Fourth, it was known that factors such as patients’ age, current smoking and/or drinking habits, the locations and sizes of ulcers, antibiotic resistance of HP , various T/Q therapy regimens and recent use of non-steroidal anti-inflammatory drugs (NSAIDs) could be identified as the effect modifiers 76–78. Baseline comparisons between arms revealed no significant differences in patients’ ages or the locations and sizes of ulcers (see online supplemental table S2).…”
Section: Discussionmentioning
confidence: 99%
“…The superiority of HP eradication strategy is mainly due to the high HP infection rates in the Japanese population, the evidence that HP eradication therapy for HP-positive patients reduces the incidence of gastric cancer by 46%, and the low cost of HP testing and eradication therapy compared to the cost of gastric cancer treatment. We previously showed that HP eradication strategy is more cost-effective than no screening [ 36 , 37 ], upper gastrointestinal series [ 38 ], and endoscopic screening [ 38 ] for gastric cancer screening and that HP eradication strategy is more cost-effective than the proton pump inhibitors therapy strategy [ 39 ] for the management of peptic ulcers in high-risk populations. This study further demonstrated the definite cost-effectiveness advantage of HP eradication strategy over endoscopic screening, even when considering various intervals or the cost of follow-up endoscopy after successful HP eradication therapy at age 50 years or older.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12]23] It is well established that eradication therapy for H. pyloriinfected patients prevents peptic ulcer onset. [25,26] Vascular lesions primarily cause upper GI bleeding in patients with eradicated H pylori infection, whereas upper GI bleeding in patients without a history of H pylori infection is primarily attributed to ulcers and erosions. Previous studies have indicated that the prophylactic prescription of proton pump inhibitors prevents upper GI bleeding.…”
Section: Upper Gi Bleedingmentioning
confidence: 99%